2019
DOI: 10.1021/acs.jpcc.9b08378
|View full text |Cite
|
Sign up to set email alerts
|

On the Stability of Cu5 Catalysts in Air Using Multireference Perturbation Theory

Abstract: An ab initio study of the interaction of O 2 , the most abundant radical and oxidant species in the atmosphere, with a Cu 5 cluster, a new generation atomic metal catalyst, is presented. The open-shell nature of the reactant species is properly accounted for by using the multireference perturbation theory, allowing the experimentally confirmed resistivity of Cu 5 clusters toward oxidation to be investigated. Approximate reaction pathways for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
49
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 18 publications
(58 citation statements)
references
References 29 publications
(58 reference statements)
5
49
1
Order By: Relevance
“…This stability of ‘atomic’ or sub-nanometer-sized Cu clusters is in stark contrast with the irreversible oxidation observed for larger Cu clusters or plasmonic nanoparticles (≈2 nm), as recently reported by Corma's group 24. Moreover, we have also observed that Cu 5 clusters deposited onto TiO 2 are stable against irreversible oxidation via the formation of CuO x oxides at temperatures higher than 700 °C,25 and display very interesting properties for electrochemical applications 26,27. In this article, we study the impact of the deposition of Cu 5 atomic clusters on the optical properties of titanium oxide, providing a thorough theoretical analysis followed by its experimental validation.…”
Section: Introductionsupporting
confidence: 73%
See 2 more Smart Citations
“…This stability of ‘atomic’ or sub-nanometer-sized Cu clusters is in stark contrast with the irreversible oxidation observed for larger Cu clusters or plasmonic nanoparticles (≈2 nm), as recently reported by Corma's group 24. Moreover, we have also observed that Cu 5 clusters deposited onto TiO 2 are stable against irreversible oxidation via the formation of CuO x oxides at temperatures higher than 700 °C,25 and display very interesting properties for electrochemical applications 26,27. In this article, we study the impact of the deposition of Cu 5 atomic clusters on the optical properties of titanium oxide, providing a thorough theoretical analysis followed by its experimental validation.…”
Section: Introductionsupporting
confidence: 73%
“…Therefore, any diffusion of clusters deposited on TiO 2 can be neglected in the given case. In fact, as stated in the introduction, the diffusion of Cu 5 clusters (and with it their agglomeration to larger, more easily oxidized nanoparticles) is observed only at temperatures as high as ≈700 °C 25. Moreover, at the adsorbed global minimum configuration shown in Fig.…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…For efficiency reasons, the geometries were first optimized at a DFT level using the B3LYP functional, and the D3 version of Grimme's dispersion correction, following by single‐point MRCI calculations. This procedure is similar to the approach employed to shed light on the reactivity of metallic clusters [83, 84] . The only difference is that here, the MECP was also optimized.…”
Section: Methodsmentioning
confidence: 99%
“…It is interesting that this collective effect favors the charge transfer from the Cu 5 cluster to the O 2 molecules when the number of O 2 molecules increases. For instance, when only one O 2 is chemisorbed at the bridge adsorption site located at the equatorial plane of the Cu 5 cluster, only a partial charge transfer is observed 1. On one hand, this partial charge transfer arises from the very favorable overlap of the π * orbital from the oxygen atoms, located at the equatorial plane of the cluster, with several d−type orbitals of the copper atoms.…”
mentioning
confidence: 99%